Dealing with carbon risk and the cost of debt: Evidence from the European market - Fabio Pizzutilo; Massimo Mariani; Alessandra Caragnano; Marianna Zito (International Journal of Financial Studies, 2020)
The ever-increasing attention towards climate change has led to investigate the economic and financial impact of environmental risk. In this scenario, we aimed at investigating the relationship between a specific component of environmental risk, namely the so-called carbon risk, and the cost of debt. This research is motivated by the fact that few studies have focused on the aforementioned relationship. We fill this gap by using a sample of companies listed on the Eurostoxx 600 Index. Our results evidence a positive relationship between carbon risk and cost of debt, providing a relevant contribution to the scarce existing literature on this topic.
Keywords: G32; M14; 330; environmental finance; carbon risk; cost of debt; European financial market